Assessment of Public Relations Strategies for Sensitisation on the Prevention of COVID-19 by Nigeria Centre for Disease Control (NCDC) - Ijese, Omole Charity; Kente, Josiah Sabo; Akase, T. M. (Darul Yasin Al Sys, 2025)
Public relations is a critical tool for guiding national affairs and addressing public health challenges. This study evaluates the public relations strategies employed by the Nigeria Centre for Disease Control (NCDC) for sensitization on COVID-19 prevention during the 2020 pandemic. The primary objective was to assess the extent, effectiveness, and scope of NCDC's public relations efforts in raising awareness and influencing preventive behavior. Adopting a cross-sectional survey research design, the study utilized questionnaires administered to a sample of 317 respondents selected through both random and purposive sampling techniques. Data were analyzed using thematic analysis, and the Extended Parallel Processing Model (EPPM) was employed as the theoretical framework. Findings revealed that 35.3% and 24% of respondents strongly agreed and agreed, respectively, that the NCDC deployed its public relations and sensitization strategies to a significant extent and in a comprehensive manner. Additionally, 62.1% of respondents affirmed the effectiveness of these strategies in enhancing public awareness and behavior change, contributing to the flattening of the COVID-19 curve, particularly in the Federal Capital Territory (FCT)—a high-risk area due to its exposure to travel-related transmission. The study concludes that public relations played a pivotal role in mitigating the spread of COVID-19 and recommends the continuous engagement of an active and well-trained public relations department at both national and state levels of the NCDC. Sustained communication efforts beyond health crises are essential to maintaining public trust and preparedness.